Back contact solar cell and method of manufacturing the same

CN122871731APending Publication Date: 2026-10-02JIANGSU RUNERGY CENTURY PHOTOVOLTAIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610957850.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-02

AI Technical Summary

Technical Problem

[0003]然而,这两种结构普遍存在以下问题:(1)N型多晶硅层中磷原子易向硅衬底过度扩散,增加界面复合;(2)P型非晶硅接触层的导电性有限,接触电阻较高;(3)激光晶化技术通常仅能实现局部晶化,接触改善区域有限;(4)正面钝化层在寄生吸收与钝化质量之间存在权衡;(5)边缘区域复合损失影响填充因子

Benefits of technology

1. 显著降低N型接触的界面复合

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122871731A_ABST
    Figure CN122871731A_ABST
Patent Text Reader

Abstract

The present disclosure provides a back contact solar cell and a preparation method thereof. The back contact solar cell comprises an N-type crystalline silicon substrate, a P-type doped region and an N-type doped region on the back of the crystalline silicon substrate. The N-type doped region comprises a first tunneling oxide layer and a carbon-doped N-type polysilicon layer arranged outwardly from the back of the crystalline silicon substrate. The P-type doped region comprises an intrinsic amorphous silicon layer, a P-type doped amorphous silicon layer and a laser-induced nanocrystalline silicon transition layer arranged outwardly from the back of the crystalline silicon substrate. According to the back contact solar cell of the present disclosure, the carbon doping in the N-type polysilicon layer can significantly reduce the interface recombination of the N-type contact; and the nanocrystallization structure of the P-type doped region takes into account the passivation quality and conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to the field of photovoltaic technology, and more specifically, to a carbon-doped dual-wavelength laser crystallization back contact solar cell and its preparation method. Background Technology

[0002] Back-contact solar cells, by placing all electrodes on the back of the cell, eliminate front-side shading losses and have become an important development direction for high-efficiency crystalline silicon solar cells. Existing back-contact solar cells are mainly divided into two categories: one is a passivated contact structure based on a "tunneling oxide layer + doped polycrystalline silicon layer", and the other is a back-contact structure based on an amorphous silicon heterojunction.

[0003] However, both structures generally have the following problems: (1) Phosphorus atoms in the N-type polycrystalline silicon layer tend to diffuse excessively into the silicon substrate, increasing interfacial recombination; (2) The conductivity of the P-type amorphous silicon contact layer is limited, and the contact resistance is high; (3) Laser crystallization technology can usually only achieve local crystallization, and the contact improvement area is limited; (4) There is a trade-off between parasitic absorption and passivation quality in the front passivation layer; (5) Recombination loss in the edge region affects the fill factor.

[0004] Therefore, a back-contact solar cell with a novel contact structure is needed to solve the above problems. Summary of the Invention

[0005] This disclosure provides a back-contact solar cell, which includes an N-type crystalline silicon substrate and a P-type doped region and an N-type doped region located on the back side of the N-type crystalline silicon substrate. The N-type doped region includes a first tunneling oxide layer and a carbon-doped N-type polycrystalline silicon layer disposed sequentially outward from the back side of the N-type crystalline silicon substrate. The P-type doped region includes an intrinsic amorphous silicon layer, a P-type doped amorphous silicon layer and a laser-induced nanocrystalline silicon transition layer disposed sequentially outward from the back side of the N-type crystalline silicon substrate.

[0006] Furthermore, in the back-contact solar cell, the carbon doping concentration of the carbon-doped N-type polycrystalline silicon layer is 1×10¹. 8 cm - ³ to 1×10¹ 9 cm - ³, phosphorus doping concentration is 1×10¹ 9 cm - ³ to 5×10¹ 9 cm - ³.

[0007] Furthermore, in the back-contact solar cell, the laser-induced nanocrystalline silicon transition layer is a layer with a gradient crystallization structure.

[0008] Furthermore, in the back-contact solar cell, the volume fraction of nanocrystalline silicon in the laser-induced nanocrystalline silicon transition layer is 20%-50% on the side closer to the N-type crystalline silicon substrate and 60%-90% on the side farther from the N-type crystalline silicon substrate.

[0009] Furthermore, the back-contact solar cell also includes a passivation antireflection layer located on the front side of the N-type crystalline silicon substrate, the front passivation antireflection layer having a structure selected from at least one of the following: (a) The intrinsic amorphous silicon layer, the N-type doped amorphous silicon layer and the silicon nitride layer, sequentially arranged from the front side of the N-type crystalline silicon substrate outwards; (b) An aluminum oxide layer and a silicon nitride layer sequentially arranged outwards from the front side of the N-type crystalline silicon substrate; and (c) A combination of (a) and (b) above.

[0010] Furthermore, the back contact solar cell also includes an isolation trench located between the P-type doped region and the N-type doped region.

[0011] Preferably, the inner surface of the isolation trench is covered with a passivation layer, the passivation layer being selected from at least one of the following: (i) Intrinsic amorphous silicon layer; (ii) A stack of aluminum oxide and silicon nitride layers; and (iii) The combination of (i) and (ii) above.

[0012] Furthermore, the back-contact solar cell also includes an edge passivation structure located at the side edge of the cell, which includes an aluminum oxide layer and a silicon nitride layer.

[0013] This disclosure also provides a method for fabricating a back-contact solar cell, comprising the following steps: depositing a carbon-doped intrinsic polycrystalline silicon layer in an N-type doped region on the back side of an N-type crystalline silicon substrate, followed by phosphorus diffusion to form a carbon-doped N-type polycrystalline silicon layer; and An intrinsic amorphous silicon layer and a P-type doped amorphous silicon layer are deposited in the P-type doped region on the back side of an N-type crystalline silicon substrate, and both are laser-processed to form a laser-induced nanocrystalline silicon transition layer.

[0014] According to the method for fabricating a back-contact solar cell disclosed herein, the laser processing employs a dual-wavelength composite laser to process the intrinsic amorphous silicon layer and the P-type doped amorphous silicon layer.

[0015] Further, the laser processing includes: a first laser processing, using a nanosecond pulsed laser with a wavelength of 532nm, an energy density of 30-50 mJ / cm², and a pulse width of 15-25ns to irradiate the entire P-type doped region; and a second laser processing, using a picosecond pulsed laser with a wavelength of 355nm, an energy density of 0.5-2 J / cm², and a pulse width of 10-50ps to selectively irradiate the portion of the P-type doped region that is in contact with the metal electrode.

[0016] According to the back-contact solar cell disclosed herein, introducing carbon doping into the N-type polycrystalline silicon layer can significantly reduce interfacial recombination at the N-type contact; and the nanocrystalline structure of the P-type doped region balances passivation quality and conductivity. Attached Figure Description

[0017] Figure 1 This is a schematic diagram of the cross-sectional structure of the carbon-doped and dual-wavelength laser crystallization back contact solar cell disclosed herein.

[0018] Figure 2 This is a process flow diagram of the method for fabricating carbon-doped and dual-wavelength laser crystallization back contact solar cells disclosed herein.

[0019] Figure 3 This is a comparison diagram of the phosphorus diffusion depth of carbon-doped N-type polycrystalline silicon layers and undoped n-poly-Si in the embodiments and comparative examples according to this disclosure.

[0020] Figure label: 110. N-type crystalline silicon substrate; 120. Front passivation antireflection layer; 131. Intrinsic amorphous silicon layer (P-type doped region); 132. P-type doped amorphous silicon layer; 133. Second transparent conductive oxide layer (P-type doped region); 134. Laser-induced nanocrystalline silicon transition layer; 141. First tunneling oxide layer; 142. Carbon-doped N-type polycrystalline silicon layer; 143. First transparent conductive oxide layer (N-type doped region); 150. Isolation trench; 151. Passivation layer; 160, 161. Metal electrodes. Detailed Implementation

[0021] To enable those skilled in the art to better understand the technical solutions of this disclosure, the technical solutions of this disclosure will be described in detail below with reference to the accompanying drawings.

[0022] Exemplary embodiments will be described more fully below with reference to the accompanying drawings; however, these exemplary embodiments may be embodied in different forms and should not be construed as limited to the embodiments set forth herein. Rather, these embodiments are provided so that this disclosure will be thorough and complete, and will enable those skilled in the art to fully understand the scope of this disclosure.

[0023] Where there is no conflict, the various embodiments of this disclosure and the features thereof in the embodiments may be combined with each other.

[0024] As used herein, the term “and / or” includes any and all combinations of one or more related enumerated entries.

[0025] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit this disclosure. As used herein, the singular forms “a” and “the” are also intended to include the plural forms unless the context clearly indicates otherwise. It will also be understood that when the terms “comprising” and / or “made of” are used in this specification, the presence of the stated feature, integral, step, operation, element, and / or component is specified, but the presence or addition of one or more other features, integrals, steps, operations, elements, components, and / or groups thereof is not excluded.

[0026] Unless otherwise stated, the concentrations mentioned in this disclosure generally refer to the weight percentage of the solute in the solution, i.e., wt%.

[0027] Unless otherwise specified, all terms used herein (including technical and scientific terms) have the same meaning as commonly understood by one of ordinary skill in the art. It will also be understood that terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the relevant art and this disclosure, and will not be interpreted as having an idealized or overly formal meaning, unless expressly so defined herein.

[0028] This disclosure provides a back-contact solar cell, such as Figure 1 As shown, it includes an N-type crystalline silicon substrate 110 and a P-type doped region and an N-type doped region located on the back side of the N-type crystalline silicon substrate 110. The N-type doped region includes a first tunneling oxide layer 141 and a carbon-doped N-type polycrystalline silicon layer 142 disposed sequentially outward from the back side of the N-type crystalline silicon substrate 110. The P-type doped region includes an intrinsic amorphous silicon layer 131, a P-type doped amorphous silicon layer 132 and a laser-induced nanocrystalline silicon transition layer 134 disposed sequentially outward from the back side of the N-type crystalline silicon substrate 110.

[0029] In the back-contact solar cell, the first tunneling oxide layer 141 is made of silicon dioxide and has a thickness of 0.5 nm to 2 nm.

[0030] Furthermore, in the back contact solar cell, the carbon doping concentration of the carbon-doped N-type polycrystalline silicon layer 142 is 1×10¹. 8 cm - ³ to 1×10¹ 9 cm - ³, phosphorus doping concentration is 1×10¹ 9 cm -³ to 5×10¹ 9 cm - ³.

[0031] The inventors discovered through research that when the carbon doping concentration is below 1×10¹ 8 cm - At concentrations below 1×10¹, the concentration of carbon atoms in the silicon lattice is insufficient to effectively occupy interstitial sites, resulting in insignificant suppression of phosphorus atom diffusion. Experiments show that carbon doping concentrations below 1×10¹ are less effective. 8 cm - At ³, the depth of phosphorus diffusion into the silicon substrate is reduced by less than 10% compared to the undoped carbon case, and the interfacial recombination parameter J0 is still higher than 0.85 fA / cm², therefore 1×10¹ 8 cm - A carbon doping concentration of 3 is the lower limit for achieving effective diffusion blocking.

[0032] When the carbon doping concentration exceeds 1×10¹ 9 cm - At 1×10¹, excessive carbon atoms can form silicon carbide (SiC) microcrystalline precipitates in the polycrystalline silicon layer or cause lattice distortion, leading to the following problems: (i) decreased crystallinity of the polycrystalline silicon layer, reduced carrier mobility, and an exponential increase in contact resistivity ρc (experiments show >10 mΩ·cm²); (ii) silicon carbide precipitates can disrupt the electrical uniformity of the polycrystalline silicon layer, resulting in deterioration of lateral conductivity; (iii) excessively high carbon concentration may also lead to an increase in the interface state density of the tunneling oxide layer, reducing passivation quality. Therefore, 1×10¹ 9 cm - The carbon doping concentration of 3 is the upper limit for maintaining good electrical performance.

[0033] The carbon doping concentration was set at 1×10¹ 8 cm - ³ to 1×10¹ 9 cm - Within the range of ³, carbon atoms are uniformly distributed in the grain boundaries and lattice gaps of polycrystalline silicon in the form of interstitial doping. This can effectively suppress the abnormal diffusion of phosphorus atoms during the high-temperature diffusion process (reducing the phosphorus diffusion depth by 40%-60%), without damaging the crystal integrity and conductivity of polycrystalline silicon.

[0034] Preferably, in the back-contact solar cell, the thickness of the carbon-doped N-type polycrystalline silicon layer is 50 nm to 150 nm.

[0035] Furthermore, in the back contact solar cell, the laser-induced nanocrystalline silicon transition layer 134 is a layer with a gradient crystallization structure.

[0036] Preferably, the volume fraction of nanocrystalline silicon in the laser-induced nanocrystalline silicon transition layer is 20%-50% on the side closer to the N-type crystalline silicon substrate 110, and the volume fraction of nanocrystalline silicon on the side farther from the N-type crystalline silicon substrate 110 is 60%-90%.

[0037] The "volume fraction of nanocrystalline silicon" refers to the volume percentage of nanoscale crystalline silicon phase in the laser-induced nanocrystalline silicon transition layer 134. Its benchmark is the total volume of the laser-induced nanocrystalline silicon transition layer 134. This volume fraction can be measured and calculated using cross-sectional transmission electron microscopy combined with energy dispersive spectroscopy (EDS) or electron diffraction patterns. Specifically, along the thickness direction of the transition layer, from the interface with the N-type crystalline silicon substrate 110 to the interface with the second transparent conductive oxide layer 133, a measurement region is selected at intervals of 5nm-10nm. The area ratio of the crystalline silicon phase within this region is calculated using image analysis software and converted into a volume fraction based on the cross-sectional thickness, thereby obtaining the volume fraction distribution curve of the crystallized region.

[0038] When the volume fraction of nanocrystalline silicon in the interface region is less than 20%, the region is dominated by amorphous silicon (>80%). Although amorphous silicon has a good chemical passivation effect on the silicon substrate surface (Si-H bond saturation dangling bond), its conductivity is extremely poor (resistivity >10). 6 The effective tunneling barrier height increases, and the tunneling probability decreases exponentially with increasing amorphous layer thickness. Experiments show that when the volume fraction of nanocrystalline silicon in the interface region is <20%, the effective tunneling barrier height increases, leading to a sharp increase in contact resistivity ρc to >50 mΩ•cm², severely impairing the fill factor. Simultaneously, an excessively high amorphous proportion easily leads to hydrogen desorption during subsequent thermal annealing, which in turn reduces passivation stability. Therefore, 20% is the lower threshold threshold for ensuring both acceptable passivation quality and tunneling conductivity in the interface region.

[0039] When the volume fraction of nanocrystalline silicon in the interface region exceeds 50%, more than half of the material in that region has been converted into nanocrystalline silicon. Although conductivity is improved, the following problems exist: (i) a large number of unsaturated dangling bonds exist at the grain boundaries of nanocrystalline silicon, becoming recombination centers, causing the interface recombination parameter J0 to increase from 0.6 fA / cm² to >1.0 fA / cm²; (ii) the growth of nanocrystalline silicon is often accompanied by epitaxial tendencies, which may destroy the originally clear c-Si / a-Si interface and introduce interface defects; (iii) excessively high crystallinity will reduce the chemical passivation effect of the intrinsic amorphous silicon layer on the silicon substrate, resulting in a 3-5 mV decrease in open-circuit voltage Voc. Therefore, 50% is the upper limit threshold for maintaining good passivation quality in the interface region.

[0040] When the volume fraction of nanocrystalline silicon in the surface region is less than 60%, this region contains a large amount of amorphous components (>40%). This region is in direct contact with the second transparent conductive oxide layer 133, requiring good lateral conductivity and low contact resistance. The carrier mobility of amorphous silicon (<1 cm² / V•s) is much lower than that of nanocrystalline silicon (10-30 cm² / V•s). Experiments show that when the volume fraction of nanocrystalline silicon in the surface region is <60%, the lateral resistance increases, and the contact resistivity with the TCO increases from about 8 mΩ•cm² to >20 mΩ•cm², significantly reducing the fill factor. Therefore, 60% is the lower threshold threshold to ensure good conductivity in the surface region.

[0041] When the volume fraction of nanocrystalline silicon in the surface region exceeds 90%, the region is almost completely crystallized. Although the conductivity is excellent, the following problems exist: (i) During the complete crystallization process, high-temperature laser treatment may completely consume the intrinsic amorphous silicon layer, and a large number of hydrogen atoms escape from the c-Si / ia-Si interface, permanently damaging the passivation effect; (ii) Over-crystallization will lead to an increase in surface roughness, affecting the uniformity and adhesion of subsequent TCO deposition; (iii) Experiments show that when the volume fraction of nanocrystalline silicon in the surface region is >90%, although ρc can be further reduced to below 5 mΩ•cm², J0 increases to >1.2 fA / cm², and the overall efficiency decreases by 0.2-0.3 percentage points. Therefore, 90% is the upper limit threshold for balancing conductivity and passivation quality.

[0042] Within the crystallization ratio range specified in this disclosure (20%-50% in the interface region and 60%-90% in the surface region), the transition layer exhibits a gradually increasing degree of crystallization from the substrate side to the surface side. Laser-induced nanocrystalline silicon transition layers with this gradual degree of crystallization offer the following synergistic advantages: (i) a high proportion of amorphous composition (50%-80%) is retained in the interface region, ensuring excellent chemical passivation of the c-Si surface (interface defect state density <1×10¹¹ cm⁻¹). - ² eV - ¹); (ii) The surface region is mainly composed of nanocrystalline silicon (60%-90%), which ensures low-resistance ohmic contact with TCO and good lateral conductivity; (iii) The gradual change in crystallinity avoids band discontinuity and interface defects caused by abrupt heterojunction, allowing photogenerated carriers to tunnel / transport smoothly to the electrode; (iv) In combination with carbon-doped N-type polycrystalline silicon layer, the entire back contact system achieves optimal matching from passivation to collection.

[0043] Furthermore, the back-contact solar cell also includes a passivation antireflection layer 120 located on the front side of the N-type crystalline silicon substrate 110.

[0044] Preferably, the passivation and antireflection layer 120 on the front side has a structure selected from at least one of the following: (a) The intrinsic amorphous silicon layer, the N-type doped amorphous silicon layer and the silicon nitride layer, sequentially arranged outward from the front side of the N-type crystalline silicon substrate 110; (b) An aluminum oxide layer and a silicon nitride layer sequentially arranged outwards from the front side of the N-type crystalline silicon substrate; and (c) A combination of (a) and (b) above.

[0045] Among them, (a) is an intrinsic amorphous silicon layer, an N-type doped amorphous silicon layer, and a silicon nitride layer in the structure; (b) is an aluminum oxide layer and a silicon nitride layer in the structure.

[0046] The passivation and antireflection layer 120 on the front side adopts the above structure, which can work well with the core structure on the back side (carbon-doped N-type polycrystalline silicon layer + dual-wavelength laser crystallization P-type contact) to achieve efficient photoelectric conversion.

[0047] In structure (a), the intrinsic amorphous silicon layer achieves excellent chemical passivation on the crystalline silicon surface, and the interface defect state density can be reduced to 1 × 10¹¹ cm⁻¹. - ² eV - ¹Below; N-type doped amorphous silicon layer can form a front surface field, effectively repelling minority carriers and reducing surface recombination; the thickness of silicon nitride layer can be 5-15 nm, and its refractive index is about 2.05, which can reduce the front reflectivity to below 5%.

[0048] The thickness of the intrinsic amorphous silicon layer can be 2-5 nm. When it is less than 2 nm, the passivation effect is insufficient, and the interface defect state density is >5×10¹¹ cm⁻¹. - ² eV - ¹; Above 5 nm, parasitic absorption increases significantly (>0.5 mA / cm²), and series resistance rises; 2-5 nm is the optimal window for balancing passivation and light transmission. By controlling the thickness of the intrinsic amorphous silicon layer within the ultrathin range of 2-5 nm, parasitic absorption loss can be controlled below 0.2 mA / cm², solving the technical problem of severe parasitic absorption in traditional amorphous silicon passivation layers (typically >10 nm thick). This approach achieves the highest open-circuit voltage (>750 mV), suitable for products pursuing extreme efficiency. The thickness of the N-type doped amorphous silicon layer can be 5-15 nm; below 5 nm, the front surface field effect is insufficient; above 15 nm, free carrier absorption increases.

[0049] In structure (b), the alumina layer utilizes its ability to fix negative charges (Qf≈10¹²-10¹³ cm⁻¹). -²) A hole accumulation layer is induced on the N-type silicon surface to achieve field-effect passivation; the silicon nitride layer has both anti-reflection and hydrogen passivation functions. This scheme completely avoids the parasitic absorption of amorphous silicon, and the short-circuit current density is increased by about 0.1-0.2 mA / cm² compared to structure (a). At the same time, the alumina / silicon nitride stack has good thermal stability and resistance to ultraviolet decay, making it suitable for products that require high current and long-term reliability.

[0050] The thickness of the alumina layer can be 1-10 nm. Below 1 nm, the field effect passivation is insufficient; above 10 nm, the deposition time is too long and may introduce stress. The thickness of the silicon nitride layer can be 50-100 nm. This thickness range can achieve optimal antireflection (refractive index matching) and hydrogen passivation effects, which is the conventional optimal range for silicon solar cells in this field.

[0051] Combining the two structures mentioned above, for example, using an intrinsic amorphous silicon / N-type doped amorphous silicon / alumina / silicon nitride stack as the passivation antireflection layer, can combine the advantages of both, further reducing surface recombination to J0<0.5 fA / cm², while controlling the front reflectivity to below 4%, which is suitable for the highest efficiency requirements.

[0052] Furthermore, the back contact solar cell also includes an isolation trench 150 located between the P-type doped region and the N-type doped region, the isolation trench having a depth of 2 μm to 10 μm and a width of 30 μm to 150 μm.

[0053] Preferably, the inner surface of the isolation trench 150 is covered with a passivation layer 151, the passivation layer 151 having at least one layer structure selected from the following: (i) Intrinsic amorphous silicon layer; (ii) A stack of aluminum oxide and silicon nitride layers; and (iii) The combination of (i) and (ii) above.

[0054] In (i), the thickness of the intrinsic amorphous silicon layer can be 5-50 nm; in (ii), the thickness of the aluminum oxide layer can be 5-10 nm, and the thickness of the silicon nitride layer can be 50-100 nm.

[0055] Furthermore, the battery also includes an edge passivation structure, which can be formed on the side edge of the battery by low-temperature plasma-assisted deposition.

[0056] Preferably, the edge passivation structure may include an aluminum oxide layer and a silicon nitride layer; wherein the thickness of the aluminum oxide layer may be 3-10 nm and the thickness of the silicon nitride layer may be 30-80 nm.

[0057] Furthermore, the back contact solar cell also includes a first transparent conductive oxide layer 143 and a second transparent conductive oxide layer 133 electrically connected to the N-type doped region and the P-type doped region.

[0058] The first transparent conductive oxide layer 143 and the second transparent conductive oxide layer 133 are each independently selected from at least one of indium tin oxide, indium tungsten oxide, aluminum-doped zinc oxide, or indium cerium oxide. Preferably, the thickness of the first transparent conductive oxide layer 143 and the second transparent conductive oxide layer 133 is 50-150 nm, and the resistivity is less than 5 × 10⁻⁶. -4 Ω·cm.

[0059] Reference Figure 2 This disclosure also provides a method for fabricating a back-contact solar cell, which includes the following steps: S101 - After depositing a carbon-doped intrinsic polycrystalline silicon layer in the N-type doped region on the back side of an N-type crystalline silicon substrate, phosphorus diffusion is performed to form a carbon-doped N-type polycrystalline silicon layer; and S102 - An intrinsic amorphous silicon layer and a P-type doped amorphous silicon layer are deposited in the P-type doped region on the back side of an N-type crystalline silicon substrate, and both are laser-processed to form a laser-induced nanocrystalline silicon transition layer.

[0060] In the method for fabricating the back contact solar cell, before forming the carbon-doped N-type polycrystalline silicon layer 142, a first tunneling oxide layer 141 is formed in the N-type doped region.

[0061] In the method for fabricating the back-contact solar cell, the laser treatment employs a dual-wavelength composite laser to treat the intrinsic amorphous silicon layer 131 and the P-type doped amorphous silicon layer 132.

[0062] Specifically, the laser processing includes: a first laser processing, which uses a nanosecond pulsed laser with a wavelength of 500nm-560nm, an energy density of 30-50 mJ / cm², and a pulse width of 15-25ns to irradiate the entire P-type doped region; and a second laser processing, which uses a picosecond pulsed laser with a wavelength of 340nm-370nm, an energy density of 0.5-2 J / cm², and a pulse width of 10-50ps to selectively irradiate the portion of the P-type doped region that is in contact with the metal electrode.

[0063] According to one embodiment of this disclosure, the method for fabricating the back-contact solar cell includes the following steps: 1) Provide N-type crystalline silicon substrate N-type single-crystal silicon wafers with resistivity of 1-10 Ω·cm and thickness of 100-200 μm (crystal orientation) can be selected. <100> The silicon wafers are then texturized on both sides using standard RCA cleaning to remove surface metallic impurities and organic contaminants.

[0064] 2) Form a passivation and antireflection layer on the front side of an N-type crystalline silicon substrate. A passivation antireflection layer can be formed on the front side of an N-type crystalline silicon substrate using known processes such as atomic layer deposition (ALD). The passivation antireflection layer can be a single layer or multiple layers; for example, a multilayer film comprising an intrinsic amorphous silicon layer, an N-type doped amorphous silicon layer, and a silicon nitride layer, or a multilayer film comprising an aluminum oxide layer and a silicon nitride layer. The total thickness of the passivation antireflection layer can be 50-150 nm.

[0065] 3) Forming an N-type doped region on the back side of an N-type crystalline silicon substrate. The N-type doped region includes a first tunneling oxide layer and a carbon-doped N-type polycrystalline silicon layer disposed sequentially outward from the back side of the crystalline silicon substrate.

[0066] Specifically, a first tunneling oxide layer 141 can be formed using low-pressure chemical vapor deposition; for example, using oxygen as the oxygen source, a SiO2 tunneling oxide layer with a thickness of 0.5-2 nm can be formed on the back side of an N-type crystalline silicon substrate. Subsequently, a carbon-doped intrinsic polycrystalline silicon layer can be formed by reactive gas deposition; for example, a carbon-doped intrinsic polycrystalline silicon layer with a thickness of 50-150 nm can be formed using silane and methane deposition, with the carbon doping concentration requirements as described above.

[0067] Then, phosphorus diffusion can be carried out in a tube diffusion furnace; for example, using POCl3 as a phosphorus source to diffuse and form a carbon-doped N-type polycrystalline silicon layer 142. The phosphorus doping concentration can be measured using the electrochemical capacitance voltage method, and the phosphorus doping concentration requirement is as described above, with the phosphorus diffusion penetration depth into the silicon substrate being less than 30 nm.

[0068] 4) Form a P-type doped region on the back side of the N-type crystalline silicon substrate. The P-type doped region includes an intrinsic amorphous silicon layer 131, a P-type doped amorphous silicon layer 132, and a laser-induced nanocrystalline silicon transition layer 134, which are sequentially disposed outward from the back side of the crystalline silicon substrate.

[0069] After partially opening windows on the back side of the N-type crystalline silicon substrate, an intrinsic amorphous silicon (ia-Si:H) layer and a P-type doped amorphous silicon (pa-Si:H) layer can be deposited sequentially using PECVD.

[0070] Subsequently, a laser-induced nanocrystalline silicon transition layer can be formed using dual-wavelength composite laser processing. First, the P-type doped region is partially irradiated using a first laser treatment; for example, a nanosecond pulsed laser with a wavelength of 500nm-560nm (preferably 532nm), an energy density of 30-50 mJ / cm², and a pulse width of 15-25ns is used to irradiate the P-type doped region. After the first laser treatment, the ia-Si / pa-Si stack is transformed into nanocrystalline silicon (nc-Si), thereby forming a laser-induced nanocrystalline silicon transition layer 134 with a grain size of 5-15nm. Then, a second laser treatment is used to selectively irradiate the strip-shaped region corresponding to the subsequent metal gate line in the P-type doped region for local fine-tuning; for example, a picosecond pulsed laser with a wavelength of 340nm-370nm (preferably 355nm), an energy density of 0.5-2 J / cm², and a pulse width of 10-50ps is used to selectively irradiate the strip-shaped region (20-50μm wide, accounting for 30%-70% of the total area of ​​the P-type region) corresponding to the subsequent metal gate line in the P-type doped region. This treatment further reduces the local contact resistivity from about 25 mΩ•cm² after the first laser treatment to below 8 mΩ•cm², while not damaging the overall transition layer structure.

[0071] Through the above-mentioned dual-wavelength composite laser processing, this disclosure realizes a P-type contact structure of "passivation + local low-resistance contact", which together with the carbon-doped N-type polycrystalline silicon layer constitutes a back carrier collection system for a high-efficiency back contact battery.

[0072] 5) A transparent conductive oxide layer is formed on the back side of an N-type crystalline silicon substrate. A transparent conductive oxide layer can be deposited on the carbon-doped N-type polycrystalline silicon layer 142 and the laser-induced nanocrystalline silicon transition layer 134 using processes such as reactive plasma deposition.

[0073] 6) Form isolation trenches on the back side of the N-type crystalline silicon substrate. An isolation trench 150 is formed between the P-type doped region and the N-type doped region using laser etching. Preferably, a passivation layer can be deposited on the inner surface of the trench, and the passivation layer can be a single layer or multiple layers of passivation film.

[0074] For example, an aluminum oxide layer can be deposited on the inner surface of the trench using atomic layer deposition first; then a silicon nitride layer can be deposited using PECVD to form a passivation layer 151.

[0075] 7) Metallize the back side of the N-type crystalline silicon substrate to form electrodes. Silver paste is printed on the back side of an N-type crystalline silicon substrate using screen printing to form a forked main gate and fine gate electrodes, which serve as metal electrodes.

[0076] According to another embodiment of this disclosure, the method for fabricating the back contact solar cell further includes a step of forming an edge passivation structure at the edge of the cell before forming the electrode.

[0077] For example, after the battery is cut and separated, Al2O3 and SiN can be deposited at the edge of the battery using methods such as plasma-enhanced atomic layer deposition. x Layers serve as edge passivation structures.

[0078] It is worth noting that, in the specific implementation of the above preparation method, the order of the steps of forming the front passivation antireflection layer, forming the N-type doped region, forming the P-type doped region, and forming the isolation trench is not fixed. Those skilled in the art can adjust the order of the specific implementation according to the process requirements.

[0079] Compared with the prior art, the back-contact solar cell and its fabrication method disclosed herein have at least the following beneficial effects: 1. Significantly reduces interfacial recombination at N-type contacts By introducing carbon doping into the N-type polycrystalline silicon layer, carbon atoms occupy interstitial positions in the silicon lattice, suppressing excessive diffusion of phosphorus atoms into the silicon substrate during high-temperature diffusion, thus making the phosphorus doping distribution more concentrated within the polycrystalline silicon layer. For example... Figure 3 As shown, compared to undoped carbon n-poly-Si, the carbon-doped n-poly-Si in the back contact solar cell of this disclosure can significantly reduce the recombination parameter J0 while maintaining a low contact resistance.

[0080] 2. Balancing passivation quality and conductivity of P-type contacts Dual-wavelength composite laser treatment is used to reduce local contact resistivity. The nanocrystalline silicon transition layer structure (retaining some amorphous components at the interface to maintain passivation, and highly crystalline surface layer to reduce resistance) balances passivation quality and conductivity.

[0081] Carbon doping exhibits excellent synergy with the dual-wavelength laser crystallization process of this invention. During laser processing, carbon atoms can serve as heterogeneous nucleation sites, promoting uniform nucleation of nanocrystalline silicon, resulting in a more concentrated grain size distribution (standard deviation <3nm), and further reducing contact resistance.

[0082] 3. The front passivation scheme is flexible and adjustable. This disclosure provides a variety of front passivation solutions for selection: an ultra-thin intrinsic amorphous silicon stack can be used to achieve optimal passivation quality, an alumina / silicon nitride stack can be used to completely eliminate parasitic absorption, or a combination of these solutions can be used. All different solutions are well compatible with the back-side core structure and can adapt to different product positioning requirements.

[0083] 4. Diverse trench passivation solutions with strong process compatibility. This disclosure also provides a variety of isolation trench passivation solutions: intrinsic amorphous silicon can be used to simplify the process, and aluminum oxide / silicon nitride stacks can be used to obtain better electric field passivation effect. Different solutions can be flexibly selected according to product requirements, and all of them are well compatible with the back core structure.

[0084] 5. Decoupling of edge passivation from main process The edge passivation structure is formed by low-temperature plasma-assisted deposition, which is decoupled from the main process route, resulting in a wider process window and applicability to substrates with different resistivity.

[0085] To enable those skilled in the art to better understand the technical solutions of this disclosure, the technical solutions of this disclosure will be described in detail below through specific embodiments.

[0086] Example 1 We provide N-type single-crystal silicon wafers with a resistivity of 3 Ω·cm and a thickness of 150 μm (Czochralski method, crystal orientation). <100> The silicon wafer was used as an N-type crystalline silicon substrate (110). Standard RCA cleaning was employed to remove surface metallic impurities and organic contaminants. A 2% KOH solution was used to perform double-sided texturing at 80°C for 15 minutes to form a pyramidal texturing structure with a pyramid height of 2-4 μm and a surface reflectivity of <11%.

[0087] Alumina (AlO) was deposited on the front side using atomic layer deposition (ALD). x A 5nm thick layer was deposited at a deposition temperature of 200℃. Then, silicon nitride (SiN) was deposited using plasma-enhanced chemical vapor deposition (PECVD). x A 75nm thick, 2.05-refractive-index layer is formed to create a front passivation and antireflection layer 120.

[0088] A tunneling oxide layer with a thickness of 1.2 nm was grown on the back side by low-pressure chemical vapor deposition and oxygen was introduced at 600°C. This was used as the first tunneling oxide layer 141.

[0089] Carbon-doped intrinsic polycrystalline silicon was deposited using a switching reactive gas deposition method, introducing silane (SiH4, 200 sccm) and methane (CH4, 20 sccm). A carbon-doped intrinsic polycrystalline silicon layer with a thickness of approximately 100 nm was deposited at 620 °C and 150 mTorr. Secondary ion mass spectrometry determined the carbon doping concentration to be 5 × 10¹. 8 cm - ³.

[0090] Phosphorus diffusion was performed in a tube diffusion furnace using POCl3 as the phosphorus source at 860°C for 40 minutes to form a carbon-doped N-type polycrystalline silicon layer 142. The phosphorus doping concentration was determined to be 3 × 10¹ using the electrochemical capacitance-voltage method. 9 cm- The phosphorus diffusion depth into the silicon substrate is <30 nm. The recombination parameter J0 extracted from the effective carrier lifetime test is 0.62 fA / cm².

[0091] After partially opening windows on the back side of the N-type crystalline silicon substrate, an intrinsic amorphous silicon (ia-Si:H) layer and a P-type doped amorphous silicon (pa-Si:H) layer were sequentially deposited using PECVD (13.56MHz) at 190℃, with the specific parameters as follows.

[0092] Intrinsic amorphous silicon (ia-Si:H) layer: 10nm thick, used as intrinsic amorphous silicon layer (131), SiH4 flow rate 100sccm, H2 flow rate 200 sccm, RF power density 20 mW / cm². P-type doped amorphous silicon (pa-Si:H) layer: 30nm thick, used as P-type doped amorphous silicon layer 132, doping gas is B2H6 (concentration 2%), B2H6 / SiH4 flow ratio is 1:50.

[0093] First laser treatment: A 532nm nanosecond pulsed laser with an energy density of 40 mJ / cm², a pulse width of 20ns, and a spot overlap rate of 70% was used to irradiate the entire P-type doped region. After treatment, the ia-Si / pa-Si stack was transformed into nanocrystalline silicon (nc-Si), forming a laser-induced nanocrystalline silicon transition layer 134 with a grain size of 5-15nm.

[0094] The second laser treatment (local fine-tuning): A 355nm picosecond pulsed laser with an energy density of 1.2 J / cm², a pulse width of 25 ps, and a spot overlap of 50% was used to selectively irradiate the strip-shaped region (35 μm wide, accounting for approximately 50% of the total area of ​​the P-type doped region) corresponding to the subsequent metal gate lines in the P-type doped region. This treatment further reduced the local contact resistivity from approximately 25 mΩ·cm² after the first laser treatment to 8 mΩ·cm².

[0095] Annealing at 200℃ for 20 minutes repairs laser-induced damage and activates doping.

[0096] An indium tungsten oxide (IWO) layer with a thickness of 100 nm was deposited on the entire back side using reactive plasma deposition at a temperature of 150 °C and an oxygen partial pressure of 1%. The resistivity of IWO is 2.5 × 10⁻⁶. -4 The charge carrier mobility is 45 cm² / V·s. A second transparent conductive oxide layer 133 is formed above the P-type doped region, and a first transparent conductive oxide layer 143 is formed above the N-type doped region.

[0097] An isolation trench 150, 80 μm wide and 5 μm deep, was formed between the P-type and N-type doped regions using 355 nm picosecond laser etching. Then, an 8 nm thick aluminum oxide (Al₂O₃) layer was deposited on the inner surface of the trench using atomic layer deposition (ALD); followed by silicon nitride (SiN) deposition using PECVD. x The layers, 70 nm thick, together form a passivation layer 151.

[0098] After the battery is cut and separated, Al2O3 (5nm) and SiN are deposited at the battery edge using plasma-enhanced atomic layer deposition. x (50nm) stack, deposition temperature 200℃.

[0099] Silver paste is screen-printed on the back side to form a forked main grid and fine grid electrodes, which serve as metal electrodes. The fine grid is 30 μm wide and 10 μm high, while the main grid is 200 μm wide. After printing, the electrodes are sintered at 250°C for 30 minutes to ensure good ohmic contact between the silver paste and the IWO.

[0100] The test was conducted under standard test conditions (AM1.5G, 1000 W / m², 25℃), and the results are as follows: Example 2 (Ultra-thin intrinsic amorphous silicon stacked layer on the front side) The only difference from Example 1 is the passivation method on the front side: a 3nm thick intrinsic amorphous silicon layer, an 8nm thick N-type doped amorphous silicon layer, and an 80nm thick silicon nitride layer are deposited. Everything else is the same as in Example 1. The efficiency of this scheme is 28.01%.

[0101] Example 3 (Trench using intrinsic amorphous silicon passivation) The difference from Example 1 is that after forming the isolation trench 150, an intrinsic amorphous silicon layer with a thickness of 20 nm is deposited conformally on the inner surface of the trench using PECVD at a deposition temperature of 190°C, a SiH4 flow rate of 50 sccm, and an H2 flow rate of 200 sccm, serving as the passivation layer 151. Alumina and silicon nitride are not deposited. The rest is the same as in Example 1. The efficiency of this scheme is 27.85%.

[0102] Example 4 (Low-Cost Solution) The difference from Example 1 is as follows: N-type contacts: Carbon doping concentration reduced to 2×10¹ 8 cm - ³, phosphorus doping concentration 2×10¹ 9 cm - ³, thickness 120nm; P-type contact: Only a single 532nm nanosecond laser treatment is used, without a secondary 355nm picosecond laser treatment; TCO material: Aluminum-doped zinc oxide (AZO) is used to replace IWO, with a thickness of 120nm; Front passivation: using AlO2 from Example 1 x / SiN x plan; Trench passivation: The intrinsic amorphous silicon scheme of Example 3 was adopted.

[0103] The efficiency of this scheme is 27.25%.

[0104] Example 5 (Thin-film solution) The N-type silicon substrate is 90 μm thick and has a resistivity of 8 Ω·cm. Front-side passivation uses AlO2 from Example 1. x / SiN x The trench passivation scheme uses the alumina / silicon nitride stack of Example 1. The rest is the same as in Example 1. Due to the thinner substrate, the energy density is appropriately reduced during back-side laser processing (30 mJ / cm² for 532nm laser and 0.8 J / cm² for 355nm laser). The efficiency of this scheme is 27.60%.

[0105] Example 6 (Carbon doping + single laser processing, no edge passivation, no isolation trench passivation) Provides N-type single-crystal silicon wafers with a resistivity of 3 Ω·cm and a thickness of 150 μm (Czochralski method, crystal orientation) <100> The silicon wafer was used as an N-type crystalline silicon substrate 110. Standard RCA cleaning was employed to remove surface metallic impurities and organic contaminants. A 2% (w / w) KOH solution was used to perform double-sided texturing at 80°C for 15 minutes to form a pyramidal texturing structure with a pyramid height of 2-4 μm and a surface reflectivity of <11%.

[0106] Alumina (AlO) was deposited on the front side using atomic layer deposition (ALD). x A 5nm thick layer was deposited at a deposition temperature of 200℃. Then, silicon nitride (SiN) was deposited using plasma-enhanced chemical vapor deposition (PECVD). x A 75nm thick, 2.05-refractive-index layer is formed to create a front passivation and antireflection layer 120.

[0107] A tunneling oxide layer with a thickness of 1.2 nm was grown on the back side by low-pressure chemical vapor deposition and oxygen was introduced at 600°C. This was used as the first tunneling oxide layer 141.

[0108] Carbon-doped intrinsic polycrystalline silicon was deposited using a switching reactive gas deposition method, introducing silane (SiH4, 200 sccm) and methane (CH4, 20 sccm). A carbon-doped intrinsic polycrystalline silicon layer with a thickness of approximately 100 nm was deposited at 620 °C and 150 mTorr. Secondary ion mass spectrometry determined the carbon doping concentration to be 5 × 10¹.8 cm - ³.

[0109] Phosphorus diffusion was performed in a tube diffusion furnace using POCl3 as the phosphorus source at 860°C for 40 minutes to form a carbon-doped N-type polycrystalline silicon layer 142. The phosphorus doping concentration was determined to be 3 × 10¹ using the electrochemical capacitance-voltage method. 9 cm - The phosphorus diffusion depth into the silicon substrate is <30 nm. The recombination parameter J0 extracted from the effective carrier lifetime test is 0.62 fA / cm².

[0110] After partially opening windows on the back side of the N-type crystalline silicon substrate, an intrinsic amorphous silicon (ia-Si:H) layer and a P-type doped amorphous silicon (pa-Si:H) layer were sequentially deposited using PECVD (13.56MHz) at 190℃, with the specific parameters as follows.

[0111] Intrinsic amorphous silicon (ia-Si:H) layer: 10nm thick, used as intrinsic amorphous silicon layer 131, SiH4 flow rate 100 sccm, H2 flow rate 200 sccm, RF power density 20 mW / cm². P-type doped amorphous silicon (pa-Si:H) layer: 30nm thick, used as P-type doped amorphous silicon layer (132), doping gas is B2H6 (concentration 2%), B2H6 / SiH4 flow ratio is 1:50.

[0112] First laser treatment: A 532nm nanosecond pulsed laser with an energy density of 40 mJ / cm², a pulse width of 20ns, and a spot overlap rate of 70% was used to irradiate the entire P-type doped region. After treatment, the ia-Si / pa-Si stack was transformed into nanocrystalline silicon (nc-Si), forming a laser-induced nanocrystalline silicon transition layer 134 with a grain size of 5-15nm. No second laser treatment was performed.

[0113] Annealing at 200℃ for 20 minutes repairs laser-induced damage and activates doping.

[0114] An indium tungsten oxide (IWO) layer with a thickness of 100 nm was deposited on the entire back side using reactive plasma deposition at a temperature of 150 °C and an oxygen partial pressure of 1%. The resistivity of IWO is 2.5 × 10⁻⁶. -4 The charge carrier mobility is 45 cm² / V·s. A second transparent conductive oxide layer 133 is formed above the P-type doped region, and a first transparent conductive oxide layer 143 is formed above the N-type doped region.

[0115] An isolation trench 150 with a width of 80 μm and a depth of 5 μm was formed between the P-type doped region and the N-type doped region using 355 nm picosecond laser etching.

[0116] Silver paste is screen-printed on the back side to form a forked main grid and fine grid electrodes, which serve as metal electrodes. The fine grid is 30 μm wide and 10 μm high, while the main grid is 200 μm wide. After printing, the electrodes are sintered at 250°C for 30 minutes to ensure good ohmic contact between the silver paste and the IWO.

[0117] Tested under standard conditions, the results are: Voc=740mV, Jsc=42.3mA / cm², FF=84.5%, η=26.5%.

[0118] Example 7 (Carbon doping + single laser treatment, complete passivation) The difference from Example 1 is that no second laser processing is performed (i.e., no dual-wavelength composite laser, only the first laser processing). The remaining steps (including the front AlO₂) are... x / SiN x Carbon-doped N-type polycrystalline silicon, trench Al2O3 / SiN x (Passivation, edge passivation, etc.) are exactly the same as in Example 1.

[0119] Performance test results: Voc=744mV, Jsc=42.65mA / cm², FF=86.48%, η=27.05%.

[0120] Comparative Example To further verify the synergistic effect of the carbon-doped N-type polycrystalline silicon layer 142 and dual-wavelength composite laser processing in this invention, the following comparative examples are provided in this section. All comparative examples use the same substrate specifications and front-side passivation scheme (AlO2) as in Example 1. x / SiN x The remaining process conditions differ only in the following key parameters.

[0121] Comparative Example 1 (No carbon doping) The difference from Example 1 is that methane (CH4) is not introduced during the deposition of the intrinsic polycrystalline silicon layer, i.e., carbon doping is not performed. The remaining steps are exactly the same as in Example 1.

[0122] Comparative Example 2 (No carbon doping + only one laser treatment) The difference from Example 1 is that: (i) no carbon doping is performed; (ii) only the first laser treatment is performed, and the second laser treatment is not performed. The remaining steps are exactly the same as in Example 1.

[0123] Comparative Example 3 (carbon doping concentration exceeds the upper limit range of this invention) The difference from Example 1 is that the methane flow rate of the carbon-doped intrinsic polycrystalline silicon layer is increased to 80 sccm, resulting in a carbon doping concentration of approximately 2 × 10¹. 9 cm -³ (Exceeding the 1×10¹ limit of this invention) 9 cm - ³ Upper limit). The remaining steps are the same as in Example 1.

[0124] Table 1 - Comparison of performance test results between Example 1 and Comparative Examples 1-3: Table 2 - Comparison of structural and performance test results for each embodiment: Results analysis: (1) Effect of carbon doping: Compared with Example 1, Comparative Example 1 showed a 6 mV decrease in Voc, a 0.63 percentage point decrease in FF, and a 0.47 percentage point decrease in efficiency. Similarly, Comparative Example 2 also showed a significant decrease in performance compared with Example 7. The main reason is the increased phosphorus diffusion depth and the rise in J0. This demonstrates the key role of carbon doping in suppressing phosphorus diffusion and reducing interfacial recombination.

[0125] (3) Synergistic effect of carbon doping and laser processing: Compared with Example 1, Comparative Example 3 showed a 10mV reduction in Voc, a 1.79 percentage point reduction in FF, and a 1.56 percentage point reduction in efficiency. The actual gain of Example 1 relative to Comparative Example 3 was 1.56 percentage points, which was higher than the sum of the individual gains of Comparative Example 1 and Comparative Example 2 (0.47 + 0.93 = 1.40), indicating a positive synergistic effect between carbon doping and dual-wavelength laser processing.

[0126] (3) Effect of dual-wavelength laser treatment: Compared with Example 1, Example 7 showed a FF reduction of 1.27 percentage points and an efficiency reduction of 0.93 percentage points. The main reason was the increase in the resistivity of the P-type contact, which proved the effect of dual-wavelength composite laser treatment on optimizing the P-type contact.

[0127] (4) Excessive carbon doping: Compared with Example 1, Comparative Example 4 showed a 5mV decrease in Voc, a 1.52 percentage point decrease in FF, and a 1.30 percentage point decrease in efficiency. This demonstrates that a higher carbon doping concentration is not necessarily better, and the scope defined by this invention is critical and non-obvious.

[0128] (5) Synergistic effect of frontal passivation: Example 2 using structure (a) achieved the highest efficiency of 28.01%, and Example 1 using structure (b) achieved an efficiency of 27.98%, both of which are superior to using AlO2 alone. x / SiN x (Efficiency approximately 27.5%) or a control group consisting of single a-Si (efficiency approximately 27.6%). This demonstrates that the various front passivation schemes provided by this invention are well compatible with the core structure of back-side carbon-doped N-type polycrystalline silicon + dual-wavelength laser crystallization P-type contact, achieving a high efficiency of over 27.98%.

[0129] Example embodiments have been disclosed herein, and while specific terminology has been used, it is for illustrative purposes only and should be construed as such, and is not intended to be limiting. In some instances, it will be apparent to those skilled in the art that features, characteristics, and / or elements described in connection with particular embodiments may be used alone, or in combination with features, characteristics, and / or elements described in connection with other embodiments, unless otherwise expressly indicated. Therefore, those skilled in the art will understand that various changes in form and detail may be made without departing from the scope of this disclosure as set forth by the appended claims.

Claims

1. A back-contact solar cell, comprising an N-type crystalline silicon substrate (110) and a P-type doped region and an N-type doped region located on the back side of the N-type crystalline silicon substrate (110), characterized in that: The N-type doped region includes a first tunneling oxide layer (141) and a carbon-doped N-type polycrystalline silicon layer (142) disposed sequentially outward from the back side of the N-type crystalline silicon substrate (110). The P-type doped region includes an intrinsic amorphous silicon layer (131), a P-type doped amorphous silicon layer (132), and a laser-induced nanocrystalline silicon transition layer (134) disposed sequentially outward from the back side of the N-type crystalline silicon substrate (110).

2. The back-contact solar cell according to claim 1, wherein, The carbon doping concentration of the carbon-doped N-type polycrystalline silicon layer (142) is 1×10¹. 8 cm - ³ to 1×10¹ 9 cm - ³, phosphorus doping concentration is 1×10¹ 9 cm - ³ to 5×10¹ 9 cm - ³.

3. The back-contact solar cell according to claim 1, wherein, The laser-induced nanocrystalline silicon transition layer (134) is a layer with a gradient crystallization structure.

4. The back-contact solar cell according to claim 1 or 3, wherein, The volume fraction of nanocrystalline silicon in the laser-induced nanocrystalline silicon transition layer is 20%-50% on the side closer to the N-type crystalline silicon substrate (110) and 60%-90% on the side farther from the N-type crystalline silicon substrate (110).

5. The back-contact solar cell according to claim 1, wherein, The back-contact solar cell further includes a passivation antireflection layer (120) located on the front side of the N-type crystalline silicon substrate (110), the front passivation antireflection layer (120) having a structure selected from at least one of the following: (a) From the front side of the N-type crystalline silicon substrate (110) outwards, an intrinsic amorphous silicon layer, an N-type doped amorphous silicon layer and a silicon nitride layer; (b) An aluminum oxide layer and a silicon nitride layer sequentially arranged outward from the front side of the N-type crystalline silicon substrate (110); and (c) A combination of (a) and (b) above.

6. The back-contact solar cell according to claim 1, wherein, The back-contact solar cell also includes an isolation trench (150) located between the P-type doped region and the N-type doped region.

7. The back-contact solar cell according to claim 6, wherein, The inner surface of the isolation trench (150) is covered with a passivation layer (151), the passivation layer (151) being selected from at least one of the following: (i) Intrinsic amorphous silicon layer; (ii) A stack of aluminum oxide and silicon nitride layers; and (iii) The combination of (i) and (ii) above.

8. The back-contact solar cell according to claim 1, wherein, The back-contact solar cell also includes an edge passivation structure located at the side edge of the cell, which includes an aluminum oxide layer and a silicon nitride layer.

9. A method for fabricating a back-contact solar cell, characterized in that, The fabrication method includes the following steps: depositing a carbon-doped intrinsic polycrystalline silicon layer in the N-type doped region on the back side of an N-type crystalline silicon substrate (110), followed by phosphorus diffusion to form a carbon-doped N-type polycrystalline silicon layer (142); and An intrinsic amorphous silicon layer (131) and a P-type doped amorphous silicon layer (132) are deposited in the P-type doped region on the back side of the N-type crystalline silicon substrate (110), and both are laser-processed to form a laser-induced nanocrystalline silicon transition layer (134).

10. The method for preparing a back-contact solar cell according to claim 9, wherein, The laser processing employs a dual-wavelength composite laser to process the intrinsic amorphous silicon layer (131) and the P-type doped amorphous silicon layer (132).

11. The method for fabricating a back-contact solar cell according to claim 10, wherein, The dual-wavelength composite laser treatment of the intrinsic amorphous silicon layer (131) and the P-type doped amorphous silicon layer (132) includes: a first laser treatment, using a nanosecond pulse laser with a wavelength of 532nm, an energy density of 30-50 mJ / cm², and a pulse width of 15-25ns to irradiate the entire P-type doped region; and a second laser treatment, using a picosecond pulse laser with a wavelength of 355nm, an energy density of 0.5-2 J / cm², and a pulse width of 10-50ps to selectively irradiate the portion of the P-type doped region that is in contact with the metal electrode.